Metabolic profiling of natural and cultured Cordyceps by NMR spectroscopy - Lu, Yi (Sci Rep, 2019)
Cordyceps, a type of Chinese herbal medicine that exhibits anti-angiogenesis and tumor growth suppression effects, has recently gained increasing popularity. However, high-quality, natural Cordyceps, such as Ophiocordyceps sinensis, is very rare and difficult to obtain in large amounts. Cordyceps is cultured instead of harvested from natural sources, but the quality with respect to the ingredients has not been fully studied. In this study, we performed an NMR metabolic profiling of aqueous extracts of Cordyceps without any sample treatment to evaluate the proper species and medium and influence of two different disinfection methods. It was discovered that Cordyceps militaris fungus and silkworm chrysalis medium were suitable for cultivation of Cordyceps. Furthermore, cordycepin, a Cordyceps-specific functional compound, was produced at different growth stages during different cultivation processes, even at the mycelial stage, and was found at three times higher concentrations in cultured C. militaris compared to that in naturally occurring C. militaris.